Train-Based Platform for Observations of the Atmosphere Composition (TROICA Project) - Elansky, N.F.; Belikov, I.B.; Lavrova, O.V.; Skorokhod, A.I.; Shumsky, R.A.; Brenninkmeijer, C.A.M.; Tarasova, O.A. (IntechOpen, 2012)
None